PERCEPTION ASSESSMENT OF A TUTORIAL PROGRAM AIMED AT INLAND STUDENTS AT A LIMA UNIVERSITY - Marcelo Torres, Nohemí Estefani (2015)
Tutorial support has become more relevant in recent years because of its implications on the socio-emotional and academic performance of students. Consequently, many universities are implementing institutional plans designed to enable students to strengthen their skills and abilities. In that sense, the study seeks to examine the perception of a group of 30 inland students, between the ages of 15 and 18, with respect to the activities developed during the 2014-1 tutorial program. A qualitative phenomenological design was used, as well as focus groups and projective techniques for the data collection process. The results indicate that students view the tutorial program as a space for support and attention, which contributes to the college-life adjustment process; however, they indicate that it should be adapted to the group’s ever-changing needs.